A study on rules of emergency procurement in PPR 2008 and its comparison with different countries procurement system during emergency - Mredha, Md. Abu Hanif (BRAC University, 2014)
This dissertation report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2012.